Comparative evaluation of GeneXpert MTB/RIF and multiplex PCR targeting mpb64 and IS6110 for the diagnosis of pleural TB. (March 2018) - Sharma, Suman; Dahiya, Bhawna; Sreenivas, Vishnubhatla; Singh, Netrapal; Raj, Ankush; Sheoran, Abhishek; Yadav, Aparna; Gupta, Krishna B; Mehta, Promod K
Aim: Diagnosis of pleural TB poses serious challenges due to paucibacillary nature of specimens and there is an urgent need to devise a reliable diagnostic test.Methods: We compared GeneXpert Mycobacterium tuberculosis /rifampin assay and the multiplex PCR (M-PCR) targeting mpb64 (Rv1980c) and IS6110 in pleural fluids (n = 78) of pleural TB patients and non-TB controls.Results: The sensitivities of 89.6 and 33.3%, and specificities of 96.7 and 100%, were observed with M-PCR and Xpert assay, respectively.Conclusion: M-PCR showed superiority over Xpert assay and may facilitate an efficient diagnosis of pleural TB. Graphical abstract: